940 Neck of Femur Fracture Management and Outcomes during COVID-19: Overview of the Results from a District General Hospital in Wales. (12th October 2021) - Waterman, J; Jayaraju, U; Nadimi, J; Morgan, D
Abstract: Introduction: The COVID-19 pandemic has delivered significant challenges to the Orthopaedic community. Our study aims to assess the impact of COVID-19 on the management and outcomes of patient's presenting with Hip Fractures to our DGH. Method: Retrospective data analysis was performed on a cohort of hip fracture patients who presented to our DGH before the COVID-19 pandemic (23/03/2019 to 05/05/2019) and were compared to those who presented during the COVID-19 pandemic (23/03/2020 to 05/05/2020). Minimum follow up was 30 days postoperatively. Results: 38 patients with hip fractures presented to our unit in the pre-COVID-19 period compared to 27 patients in the COVID-19 period. Total time from presentation to discharge, during COVID-19, demonstrated a 70.23% decrease when compared to the pre-COVID cohort. 30-day Mortality rates were higher in the COVID-19 cohort. Conclusions: During the COVID-19 pandemic our time to theatre and discharge of hip fractures has seen an improvement, with time to discharge decreasing by 70.23%. Comparison of our mortality rates has seen a fourfold increase likely influenced by the detrimental effects of COVID-19. Further work and larger numbers are required to see the true impact of COVID-19 on the management and outcomes of hip fractures in our DGH.